DNA hypomethylation leads to cGAS‐induced autoinflammation in the epidermis. (29th September 2021) - Beck, Mirjam A; Fischer, Heinz; Grabner, Lisa M; Groffics, Tamara; Winter, Mircea; Tangermann, Simone; Meischel, Tina; Zaussinger‐Haas, Barbara; Wagner, Patrick; Fischer, Carina; Folie, Christina; Arand, Julia; et al.
Abstract: DNA methylation is a fundamental epigenetic modification, important across biological processes. The maintenance methyltransferase DNMT1 is essential for lineage differentiation during development, but its functions in tissue homeostasis are incompletely understood. We show that epidermis‐specific DNMT1 deletion severely disrupts epidermal structure and homeostasis, initiating a massive innate immune response and infiltration of immune cells. Mechanistically, DNA hypomethylation in keratinocytes triggered transposon derepression, mitotic defects, and formation of micronuclei. DNA release into the cytosol of DNMT1‐deficient keratinocytes activated signaling through cGAS and STING, thus triggering inflammation. Our findings show that disruption of a key epigenetic mark directly impacts immune and tissue homeostasis, and potentially impacts our understanding of autoinflammatory diseases and cancer immunotherapy. Synopsis: In DNMT1 deficient keratinocytes, DNA hypomethylation induces transposon derepression, mitotic defects and formation of micronuclei. DNA released into the cytosol by micronulear rupture activates signalling through cGAS and STING, further activating inflammation by ISG induction. DNMT1 ablation in the epidermis triggers a strong pathological innate immune response and disruption of the skin structure DNA hypomethylation in keratinocytes leads to the formation of micronuclei and cytosolic DNA accumulation thereby activating a cGAS dependent immune response The epigenetic methyl‐CpG mark has an important role in immune and tissue homeostasis Autoinflammation of the skin is a direct consequence of DNA hypomethylation upon loss of DNMT1 in vivo Abstract : Deletion of maintenance methyltransferase DNMT1 in keratinocytes causes formation of micronuclei, whose rupture and cytosolic DNA release activates inflammatory signalling via cGAS/STING.